Residual inflammatory risk appeared related to weight, atherogenic lipid profile and biomarkers of inflammation, but not to glycaemic control in type 1 diabetes. (3rd October 2022) - J Johansen, N; Dejgaard, T F; Lund, A; Moeller, H J; Forman, J; Vilsboell, T; Andersen, H U; Knop, F K
Abstract: Background: Mortality associated with atherosclerotic cardiovascular disease reduces average life expectancy by more than a decade in type 1 diabetes. Systemic inflammation drives atherosclerosis, and the concept of residual inflammatory risk (defined by high-sensitivity C-reactive protein (hsCRP) ≥2 mg/l) poses a potential, new therapeutic target for lowering residual cardiovascular risk in type 1 diabetes. However, the characteristics of individuals with residual inflammatory risk in type 1 diabetes are unknown. Purpose: Identify differences in relevant demographics, clinical and paraclinical parameters for individuals with residual inflammatory risk as compared to those without in type 1 diabetes. Methods: Baseline characteristics as stratified for CRP ≥2 mg/l were analysed in 105 patients with type 1 diabetes participating in a previously published clinical trial. The study population was sampled to represent the broad background population struggling with glycaemic control and with a high cardiovascular risk. Results: Residual inflammatory risk was seen in 39.1% of the study population. Compared to individuals without residual inflammatory risk, individuals with residual inflammatory risk were more frequently women, had increased body weight, body mass index and dual-energy X-ray absorptiometry (DXA)-assessed fat mass and exhibited elevated levels of low-density lipoprotein (LDL), very low-density lipoprotein (VLDL) and total cholesterol as well as triglycerides, interleukin 6 and tumour necrosis factor alpha (Table 1). Glycated haemoglobin, blood pressure and markers of renal function were similar between groups (Table 1). Conclusion: In the present cohort of individuals with type 1 diabetes, residual inflammatory risk was seen in 39.1% (similar to what is observed outside of type 1 diabetes) and appeared related to overweight/obesity, an atherogenic lipid profile and circulating biomarkers of inflammation but not to glycaemic control, blood pressure or renal function. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): AstraZenecaHerlev Gentofte Hospital